Leadership Style of the Principal in Mas Al-Asy'ariyah Islamic School Medan Krio - Hendri Fauza; Mhd Irgi Fahreza (Education Achievement: Journal of Science and Research, 2023)
This research is motivated by the leadership style of the principal in MAS Al-Asy'ariyah Medan Krio. Ensuring the leadership style of the school principal is one of the mandatory duties of the school principal in enhancing the leadership style at MAS Al-Asy'ariyah Medan Krio. This study aims to examine the leadership of the school principal in the leadership style at MAS Al-Asy'ariyah Medan Krio. The research method used in this study is descriptive qualitative research, where the researcher will describe the leadership style of the school principal at MAS Al-Asy'ariyah Medan Krio. There are three participants in this study, namely the school principal, teachers, and students at MAS Al-Asy'ariyah Medan Krio. The research findings indicate that: 1) The principal of MAS Al-Asy'ariyah Medan Krio implements effective leadership processes, including supervision, planning, and execution in the leadership style of the school principal. 2) The principal also frequently motivates teachers and students with the aim of encouraging them to adopt the leadership style of the school principal, thereby achieving the goals in the leadership style at MAS Al-Asy'ariyah Medan Krio. 3) The principal demonstrates good role modeling by involving the community in all school activities, aiming to receive input and active participation from the community in improving the leadership style at MAS Al-Asy'ariyah Medan Krio. In conclusion, the leadership of the school principal in enhancing the leadership style at MAS Al-Asy'ariyah Medan Krio has been effective without any obstacles, as the principal performs all tasks using a well-organized management system.